AS RELAÇÕES ENTRE GESTÃO DA DIVERSIDADE E CULTURA ORGANIZACIONAL EM UMA EMPRESA DO SETOR PORTUÁRIO DO RIO DE JANEIRO - COELHO, FELIPE COSTA (2016)
The organization’s culture is important to maintain employees with the same goals and values. However, in order to maintain a competitive strategy and act responsibly in the community, the company needs to innovate and adapt. The diversity management is valid so it is able to keep facing these new challenges e demands. However, there are many obstacles to successfully diversity management. This study has the purpose to understand how diversity management can affect an organization’s culture. In addition, how that culture can affect the strategy to implement management for the diversity. For this study, a case study with six interviews were used. The interviews were support by a semi-structured script. All the data were examined by content analysis. According to the accomplished research, organizational culture and diversity management are directly connected and can affect positivity to each other, as long as they are in equilibrium, otherwise, they will cause disadvantages to the organization.